Histoplasma Virulence and Host Responses - Mircea Radu Mihu; Joshua Daniel Nosanchuk (International Journal of Microbiology)
Histoplasma capsulatum is the most prevalent cause of fungal respiratory disease. The disease extent and outcomes are the result of the complex interaction between the pathogen and a host's immune system. The focus of our paper consists in presenting the current knowledge regarding the multiple facets of the dynamic host-pathogen relationship in the context of the virulence arsenal displayed by the fungus and the innate and adaptive immune responses of the host.